Don't fear AI (Volume 2) - Atkinson, Robert (European Investment Bank, 2019)
Over the last decade, Europe and most advanced economies have experienced a decline in productivity, leading to political unrest and rising uncertainty about the future. A new production revolution, enabled in part by artificial intelligence (AI), is now emerging, bringing a new wave of technologies, but there are widespread fears that these changes will also bring a big rise in unemployment as machines replace human beings in large numbers. History tells us that we should not be afraid of industrial change. AI will take over some tasks, but this will not happen all of a sudden and there will be plenty of work left for humans. Restricting or slowing down new technology will not help the world economy. Instead, nations need to help people adjust to more technically advanced jobs, while education should focus more on "21st century skills" such as teamwork and critical thinking. These are our next real challenges. This is the second essay in the Big Ideas series created by the European Investment Bank. The EIB has invited international thought leaders to write about the most important issues of the day. These essays are a reminder that we need new thinking to protect the environment, promote equality and improve people's lives around the globe.